Erosive lichen planus of the vulva: weak circulating basement membrane zone antibodies are present. - Cooper, S; Dean, D; Allen, J; Kirtschig, G; Wojnarowska, F (2005)
The objective of this study was to investigate whether circulating basement membrane zone (BMZ) antibodies are present in erosive lichen planus (LP) of the vulva. In total, 56 consecutive women with biopsy-confirmed erosive LP of the vulva were recruited from a vulval clinic in a district general hospital and teaching hospital in Oxfordshire. Indirect immunofluorescence (IgG and IgA) was performed on 56 sera, and 15 were tested to IgG subclasses (1-4). Immunoblotting was carried out on salt-split and urea-extracted epidermal skin extracts on 11. The main outcome measure was the presence or absence of staining at the BMZ. Of the 56 sera, 34 (61%) had weak (neat or 1 : 5) epidermal-binding BMZ antibodies (25 had IgG, 5 had IgA, 4 had both IgG and IgA). All 15 sera tested to IgG showed epidermal binding to one or more IgG subclasses: IgG1 (7 sera), IgG2 (7), IgG3 (7) and IgG4 (0). Immunoblotting identified IgG antibodies to bullous pemphigoid (BP)180 (10/11) and BP230 (2/11). The majority (61%) of patients with vulval erosive LP had circulating serum IgG BMZ antibodies, chiefly reacting with BP180. There was subclass restriction of the IgG response to IgG1, 2 and 3. The significance of these antibodies is uncertain, but they may be a marker for the disease.